High-temperature-resistant TPU material and preparation method thereof
By preparing functionalized polyurethane, modified polyphosphazene microspheres, and modified nano-calcium carbonate, the high-temperature resistance, flame retardancy, and anti-aging properties of thermoplastic polyurethane materials were improved, solving the problems of flammability and aging of thermoplastic polyurethane and achieving stable use in high-temperature environments.
Patent Information
- Application Number
- CN202511544805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-10-28
AI Technical Summary
Thermoplastic polyurethane materials are flammable, prone to aging, and have poor thermal stability, failing to meet the requirements for high-temperature resistant materials, and their mechanical properties decrease at high temperatures.
The flame retardancy, anti-aging and high temperature resistance of materials are improved by preparing functionalized polyurethane, modified polyphosphazene microspheres and modified nano-calcium carbonate. The specific steps include prepolymerization, chain extension reaction, mixing and extrusion molding.
The material's high-temperature resistance, flame retardancy, and anti-aging properties have been improved, meeting the requirements for use in high-temperature environments.
Smart Images

Figure SMS_4 
Figure SMS_5 
Figure SMS_6
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of high polymer materials, in particular to a high-temperature-resistant TPU material and a preparation method thereof. BACKGROUND
[0002] As an important part of the high polymer material field, thermoplastic polyurethane has been widely used in high-end fields such as aerospace, construction, new energy vehicle manufacturing and electronic devices since its first synthesis, due to its special structure of soft and hard segments and many advantages such as high elasticity, low temperature resistance, wear resistance, recyclability and processability. In recent years, with the rapid development of the new energy vehicle field and the electronic and electrical industry, the market of thermoplastic polyurethane is becoming more and more open, and has broad development space. However, thermoplastic polyurethane is still limited by its major defects of flammability, easy aging and poor thermal stability.
[0003] When thermoplastic polyurethane is at a temperature above 80℃ for a long time, some main mechanical properties such as modulus and strength will decrease, and when the processing temperature reaches or exceeds 200℃, the polyurethane will undergo thermal degradation, which cannot meet the requirements of high-temperature-resistant materials. The limiting oxygen index value LOI of thermoplastic polyurethane is only 17%~19%, which belongs to flammable materials, and a large amount of toxic gases will be released during combustion, threatening people's life and property safety, so it is abandoned in many application fields. The urethane bond and ether bond in thermoplastic polyurethane are sensitive to ultraviolet light, and long-term exposure will cause photo-oxidation reaction, leading to molecular chain rupture and structure damage, which finally manifests as surface powdering, cracking and decrease of mechanical properties.
[0004] In view of the problems existing in thermoplastic polyurethane, a thermoplastic polyurethane material with anti-aging, flame-retardant and high-temperature-resistant properties is invented to improve the comprehensive performance of thermoplastic polyurethane and meet the growing market demand. SUMMARY
[0005] The present application aims to provide a high-temperature-resistant TPU material and a preparation method thereof to solve the problems in the prior art.
[0006] To solve the above technical problems, the present application provides the following technical scheme: A high-temperature-resistant TPU material is prepared by pre-polymerizing polyether diol and toluene-2,4-diisocyanate, and then chain extending with soybean genin dianhydride monomer to obtain functionalized polyurethane; modifying polyphosphazene microspheres by reacting polyphosphazene microspheres and 4-allyl-2,6-di-tert-butylphenol to obtain modified polyphosphazene microspheres; modifying nano calcium carbonate by reacting pre-modified nano calcium carbonate and 3-hydroxy-beta-ionone to obtain modified nano calcium carbonate; and mixing the functionalized polyurethane, the modified polyphosphazene microspheres and the modified nano calcium carbonate uniformly, and then extruding and molding to obtain the high-temperature-resistant TPU material. The daidzein dianhydride monomer is prepared by reacting daidzein and phthalic anhydride-4-formyl chloride; The polyphosphazene microspheres are prepared by reacting hexachlorocyclotriphosphazene, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine and 2-(mercaptomethyl)benzene-1,4-diol; The pre-modified nano calcium carbonate is prepared by reacting nano calcium carbonate and chloropropyl triethoxysilane.
[0007] A preparation method of a high-temperature-resistant TPU material, comprising the following preparation steps: (1) polyether glycol, daidzein dianhydride monomer and toluene-2,4-diisocyanate are weighed according to the molar ratio of 1:(0.5-0.6):(1.8-2.0); daidzein dianhydride monomer and N,N-dimethylformamide are mixed uniformly according to the mass ratio of 1:(5-6) to prepare a dianhydride solution; polyether glycol and N,N-dimethylformamide are mixed uniformly according to the mass ratio of 1:(8-10), heated to 70-80°C, and then toluene-2,4-diisocyanate and 0.04-0.06 times the mass of polyether glycol of dibutyltin dilaurate are sequentially added under a nitrogen atmosphere, and stirred at 70-80°C and 200-300 r / min for 50-60 min; the dianhydride solution is added, and stirring is continued at 75-85°C for 1-2 h; the temperature is raised to 110°C, and stirring is continued for 2-3 h; and drying is performed under vacuum at 60-70°C for 18-20 h to obtain a functional polyurethane; (2) polyphosphazene microspheres, 4-allyl-2,6-di-tert-butylphenol and N,N-dimethylformamide are mixed uniformly according to the mass ratio of 1:(3-4):(20-30), 0.06-0.08 times the mass of polyphosphazene microspheres of azobisisobutyronitrile is added, stirring is performed at 70-80°C and 300-500 r / min for 4-5 h, filtration is performed, washing is performed with anhydrous ethanol for 5 times, and drying is performed under vacuum at 50-60°C for 18-20 h to obtain modified polyphosphazene microspheres; (3) pre-modified nano calcium carbonate, 3-hydroxy-β-ionone, triethylamine and N,N-dimethylformamide are mixed uniformly according to the mass ratio of 1:(3-4):(0.1-0.2):(20-30), stirring is performed at 55-65°C and 300-500 r / min for 5-6 h, filtration is performed, washing is performed with anhydrous ethanol and deionized water for 3 times each, and drying is performed under vacuum at 60-70°C for 16-18 h to obtain modified nano calcium carbonate; (4) by mass parts, take 98~100 parts of functional polyurethane, 5~6 parts of modified polyphosphazene microspheres, 4~5 parts of modified nano calcium carbonate; the functional polyurethane, modified polyphosphazene microspheres, modified nano calcium carbonate are mixed uniformly, placed in the extruder, the extrusion temperature is 190~210℃, the screw rotation speed is 20~30r / min, and the high temperature resistant TPU material is prepared.
[0008] As optimization, the type of polyether diol in step (1) is PPG-1000.
[0009] As optimization, the preparation method of daidzein dianhydride monomer in step (1) is: daidzein, phthalic anhydride-4-formyl chloride are added to toluene with 20~30 times the mass of daidzein, 0.06~0.08 times the mass of daidzein of pyridine is added, stirring at room temperature at 300~500r / min for 60~70min, heating to 100~110℃, continuing to stir under nitrogen atmosphere for 4~5h, drying under vacuum at 55~65℃ for 10~12h, and daidzein dianhydride monomer is prepared; the reaction mechanism is as follows: .
[0010] As optimization, the preparation method of polyphosphazene microspheres in step (2) is: mix hexachlorocyclotriphosphazene and acetonitrile uniformly in a mass ratio of 1:(50~60), ultrasonic at room temperature for 1~2h, add 1~1.2 times the molar amount of hexachlorocyclotriphosphazene 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine, add 0.7~0.8 times the molar amount of hexachlorocyclotriphosphazene 2-(mercaptomethyl)benzene-1,4-diol, continue to ultrasonic for 10~20min, add 0.06~0.08 times the mass of hexachlorocyclotriphosphazene triethylamine, stir at 30~40℃ at 200~300r / min for 5~6h, naturally cool to room temperature, stand for 6~8h, filter, wash with anhydrous ethanol and deionized water for 3 times, dry under vacuum at 50~60℃ for 12~14h, and polyphosphazene microspheres are prepared.
[0011] As optimization, the CAS number of 2-(mercaptomethyl)benzene-1,4-diol is 5273-75-6; the structural formula is: .
[0012] As optimization, the preparation method of the pre-modified nano calcium carbonate in step (3) is as follows: nano calcium carbonate and anhydrous ethanol are uniformly mixed at a mass ratio of 1:(60-70), ultrasonic treatment is conducted at room temperature for 1-2 hours, 5-6 times nano calcium carbonate of chloropropyl triethoxysilane is added, the temperature is increased to 70-80 DEG C, ultrasonic treatment is continuously conducted for 8-10 minutes, 7-8 times nano calcium carbonate of 1 mol / L oxalic acid aqueous solution is added at a constant speed within 10 minutes, after the addition is completed, stirring is continuously conducted for 3-4 hours, filtration is conducted, anhydrous ethanol and deionized water are used for washing for 3 times respectively, and the pre-modified nano calcium carbonate is prepared under vacuum condition at 60-70 DEG C for 10-12 hours.
[0013] As optimization, the CAS number of the 3-hydroxy-beta-ionone in step (3) is 116296-75-4; the structural formula is as follows: .
[0014] Compared with the prior art, the present application has the following beneficial effects: In the preparation of the high-temperature-resistant TPU material, soybean genin dianhydride monomers are prepared by reacting soybean genin and phthalic anhydride-4-formyl chloride; functional polyurethane is prepared by pre-polymerizing polyether glycol and toluene-2,4-diisocyanate and then chain extending with the soybean genin dianhydride monomers; polyphosphazene microspheres are prepared by reacting hexachlorotriphosphazene, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine and 2-(mercaptomethyl)benzene-1,4-diol; modified polyphosphazene microspheres are prepared by reacting the polyphosphazene microspheres and 4-allyl-2,6-di-tert-butylphenol; modified nano calcium carbonate is prepared by sequentially reacting nano calcium carbonate with chloropropyl triethoxysilane and 3-hydroxy-beta-ionone; and the high-temperature-resistant TPU material is prepared by uniformly mixing the functional polyurethane, the modified polyphosphazene microspheres and the modified nano calcium carbonate and then extruding and molding.
[0015] First, soybean genin dianhydride monomers are prepared by reacting soybean genin and phthalic anhydride-4-formyl chloride; functional polyurethane is prepared by pre-polymerizing polyether glycol and toluene-2,4-diisocyanate and then chain extending with the soybean genin dianhydride monomers; imide groups and soybean genin are introduced into the main chain of the functional polyurethane; the introduction of the imide groups can improve the high-temperature resistance of the high-temperature-resistant TPU material, the soybean genin contains a deoxybenzoin structure and has high carbon formation capacity, so that a dense carbon layer structure can be formed in the material during combustion, thereby improving the flame retardant performance of the high-temperature-resistant TPU material.
[0016] Secondly, the polyanaphthalene microspheres are prepared by the reaction of hexachlorocyclotriphosphazene, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine and 2-(mercaptomethyl)benzene-1,4-diol, so that the cyclotriphosphazene skeleton, the triazine structure and the mercapto group are contained in the polyanaphthalene microspheres; the addition reaction of the mercapto group on the polyanaphthalene microspheres and the carbon-carbon double bond on 4-allyl-2,6-di-tert-butylphenol is carried out to prepare the modified polyanaphthalene microspheres, and the 2,6-di-tert-butylphenol structure is grafted on the modified polyanaphthalene microspheres; the triazine structure can improve the flame retardation and high-temperature resistance of the high-temperature-resistant TPU material, the cyclotriphosphazene skeleton can improve the flame retardation of the high-temperature-resistant TPU material, and the grafted 2,6-di-tert-butylphenol structure belongs to a hindered phenolic light stabilizer, which can delay the photoaging of the material by capturing free radicals and interrupting the oxidation chain reaction, thereby improving the anti-aging performance of the high-temperature-resistant TPU material.
[0017] Finally, the pre-modified nano calcium carbonate is prepared by the reaction of nano calcium carbonate and chloropropyl triethoxysilane, and the chlorine atom is introduced on the pre-modified nano calcium carbonate; the chlorine atom introduced on the pre-modified nano calcium carbonate reacts with the hydroxyl group on 3-hydroxy-β-ionone to prepare the modified nano calcium carbonate, and the β-ionone structure is introduced on the modified nano calcium carbonate; the β-ionone structure has a photoisomerization effect, and is converted from the trans conformation to the cis conformation under the action of ultraviolet light, and returns to the trans conformation under the condition of avoiding light, so that the reversible cis-trans isomerization change endows the β-ionone with the performance of ultraviolet absorption, converts the ultraviolet light energy into chemical energy, and thus improves the anti-aging performance of the high-temperature-resistant TPU material; the addition of the nano calcium carbonate in the polyurethane can improve the dimensional stability and heat resistance of the material, and thus improves the high-temperature resistance of the high-temperature-resistant TPU material. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
[0019] Embodiment 1: A preparation method of a high-temperature-resistant TPU material, the preparation method of the high-temperature-resistant TPU material comprising the following preparation steps: (1) soybean genistin, phthalic anhydride-4-formyl chloride are added to toluene with 20 times the mass of soybean genistin according to a molar ratio of 1:2, 0.06 times the mass of pyridine of soybean genistin is added, stirring at 300 r / min for 70 min at room temperature, the temperature is raised to 100℃, and the stirring is continued for 5 h under a nitrogen atmosphere, and the product is dried under vacuum at 55℃ for 12 h to obtain soybean genistin dianhydride monomer; polyether diol, soybean genistin dianhydride monomer, and toluene-2,4-diisocyanate are weighed according to a molar ratio of 1:0.5:1.8; the soybean genistin dianhydride monomer and N,N-dimethylformamide are mixed uniformly according to a mass ratio of 1:5 to prepare a dianhydride solution; the polyether diol and N,N-dimethylformamide are mixed uniformly according to a mass ratio of 1:8, heated to 70℃, and then toluene-2,4-diisocyanate and 0.04 times the mass of dibutyltin dilaurate of the polyether diol are added under a nitrogen atmosphere, stirring at 70℃ and 200 r / min for 60 min, then the dianhydride solution is added, and the stirring is continued at 75℃ for 2 h, the temperature is raised to 110℃, and the stirring is continued for 3 h, and the product is dried under vacuum at 60℃ for 20 h to obtain a functional polyurethane; (2) hexachlorocyclotriphosphazene and acetonitrile are mixed uniformly according to a mass ratio of 1:50, and ultrasonic treatment is performed for 1 h at room temperature, 1 times the molar amount of 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine of hexachlorocyclotriphosphazene is added, 0.7 times the molar amount of 2-(mercaptomethyl)benzene-1,4-diol of hexachlorocyclotriphosphazene is added, and ultrasonic treatment is continued for 10 min, 0.06 times the mass of triethylamine of hexachlorocyclotriphosphazene is added, stirring is performed at 200 r / min for 6 h at 30℃, the temperature is allowed to cool to room temperature naturally, the product is allowed to stand for 6 h, filtration is performed, the product is washed with anhydrous ethanol and deionized water for 3 times each, and the product is dried under vacuum at 50℃ for 14 h to obtain polyphosphazene microspheres; the polyphosphazene microspheres, 4-allyl-2,6-di-tert-butylphenol, and N,N-dimethylformamide are mixed uniformly according to a mass ratio of 1:3:20, 0.06 times the mass of azobisisobutyronitrile of the polyphosphazene microspheres is added, stirring is performed at 300 r / min for 5 h at 70℃, filtration is performed, the product is washed with anhydrous ethanol for 5 times, and the product is dried under vacuum at 50℃ for 20 h to obtain modified polyphosphazene microspheres; (3) The nano calcium carbonate and anhydrous ethanol were mixed uniformly at a mass ratio of 1:60, and ultrasonic treatment was performed for 1 h at room temperature. Then, 5 times the mass of the nano calcium carbonate of chloropropyl triethoxysilane was added, and the temperature was increased to 70°C. Ultrasonic treatment was continued for 10 min. Then, 7 times the mass of the nano calcium carbonate of a 1 mol / L oxalic acid aqueous solution was added at a uniform speed within 10 min. After the addition was completed, stirring was continued for 4 h. Filtration was performed, and the product was washed with anhydrous ethanol and deionized water for 3 times. The product was dried at 60°C under vacuum for 12 h to obtain the pre-modified nano calcium carbonate. The pre-modified nano calcium carbonate, 3-hydroxy-beta-ionone, triethylamine, and N,N-dimethylformamide were mixed uniformly at a mass ratio of 1:3:0.1:20. Stirring was performed at 55°C and 300 r / min for 6 h. Filtration was performed, and the product was washed with anhydrous ethanol and deionized water for 3 times. The product was dried at 60°C under vacuum for 18 h to obtain the modified nano calcium carbonate. (4) The functional polyurethane was 98 parts by mass, the modified polyphosphazene microspheres were 5 parts by mass, and the modified nano calcium carbonate was 4 parts by mass. The functional polyurethane, the modified polyphosphazene microspheres, and the modified nano calcium carbonate were mixed uniformly and extruded into a shape in an extruder. The extrusion temperature was 190°C, and the screw rotation speed was 20 r / min. A high-temperature-resistant TPU material was obtained.
[0020] Embodiment 2: A preparation method of a high-temperature-resistant TPU material, the preparation method comprising the following preparation steps: (1) Soybean genin and phthalic anhydride-4-formyl chloride were added to 25 times the mass of the soybean genin in toluene at a molar ratio of 1:2. Pyridine was added at 0.07 times the mass of the soybean genin. Stirring was performed at room temperature and 400 r / min for 65 min. The temperature was increased to 105°C. Stirring was continued under a nitrogen atmosphere for 4.5 h. The product was dried at 60°C under vacuum for 11 h to obtain a soybean genin dianhydride monomer. Polyether diol, soybean genin dianhydride monomer, and toluene-2,4-diisocyanate were taken at a molar ratio of 1:0.55:1.9. The soybean genin dianhydride monomer and N,N-dimethylformamide were mixed uniformly at a mass ratio of 1:5.5 to prepare a dianhydride solution. The polyether diol and N,N-dimethylformamide were mixed uniformly at a mass ratio of 1:9. Heating was performed to 75°C. Toluene-2,4-diisocyanate and 0.05 times the mass of the polyether diol of dibutyltin dilaurate were added in sequence under a nitrogen atmosphere. Stirring was performed at 75°C and 250 r / min for 55 min. The dianhydride solution was added. Stirring was continued at 80°C for 1.5 h. The temperature was increased to 110°C. Stirring was continued for 2.5 h. The product was dried at 65°C under vacuum for 19 h to obtain a functional polyurethane. (2) mixing hexachlorocyclotriphosphazene and acetonitrile uniformly according to a mass ratio of 1:55, ultrasonicating at room temperature for 1.5 hours, adding 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine in a molar amount of 1.1 times that of hexachlorocyclotriphosphazene, adding 2-(mercaptomethyl)benzene-1,4-diol in a molar amount of 0.75 times that of hexachlorocyclotriphosphazene, continuing to ultrasonicate for 15 minutes, adding triethylamine in a mass of 0.07 times that of hexachlorocyclotriphosphazene, stirring at 35℃ and 250r / min for 5.5 hours, naturally cooling to room temperature, standing for 7 hours, filtering, washing with anhydrous ethanol and deionized water for 3 times respectively, and drying at 55℃ under vacuum for 13 hours to obtain polyphosphazene microspheres; mixing the polyphosphazene microspheres, 4-allyl-2,6-di-tert-butylphenol and N,N-dimethylformamide uniformly according to a mass ratio of 1:3.5:25, adding azobisisobutyronitrile in a mass of 0.07 times that of the polyphosphazene microspheres, stirring at 75℃ and 400r / min for 4.5 hours, filtering, washing with anhydrous ethanol for 5 times, and drying at 55℃ under vacuum for 19 hours to obtain modified polyphosphazene microspheres; (3) mixing nano calcium carbonate and anhydrous ethanol uniformly according to a mass ratio of 1:65, ultrasonicating at room temperature for 1.5 hours, adding chloropropyltriethoxysilane in a mass of 5.5 times that of the nano calcium carbonate, increasing the temperature to 75℃, continuing to ultrasonicate for 9 minutes, adding oxalic acid aqueous solution in a concentration of 1mol / L at a uniform speed within 10 minutes, adding oxalic acid aqueous solution in a mass of 7.5 times that of the nano calcium carbonate, continuing to stir for 3.5 hours after the addition is completed, filtering, washing with anhydrous ethanol and deionized water for 3 times respectively, and drying at 65℃ under vacuum for 11 hours to obtain pre-modified nano calcium carbonate; mixing the pre-modified nano calcium carbonate, 3-hydroxy-β-ionone, triethylamine and N,N-dimethylformamide uniformly according to a mass ratio of 1:3.5:0.15:25, stirring at 60℃ and 400r / min for 5.5 hours, filtering, washing with anhydrous ethanol and deionized water for 3 times respectively, and drying at 65℃ under vacuum for 17 hours to obtain modified nano calcium carbonate; (4) according to mass parts, taking 99 parts of functionalized polyurethane, 5.5 parts of modified polyphosphazene microspheres and 4.5 parts of modified nano calcium carbonate; mixing the functionalized polyurethane, the modified polyphosphazene microspheres and the modified nano calcium carbonate uniformly, and extruding into a shape in an extruder, the extrusion temperature is 200℃, and the screw rotation speed is 25r / min, to obtain a high-temperature-resistant TPU material.
[0021] Example 3: a preparation method of a high-temperature-resistant TPU material, the preparation method of the high-temperature-resistant TPU material comprising the following preparation steps: (1) soybean genistin, phthalic anhydride-4-formyl chloride are added to toluene with 30 times the mass of soybean genistin according to a molar ratio of 1:2, 0.08 times the mass of pyridine of soybean genistin is added, stirring at 500 r / min for 70 min at room temperature, the temperature is raised to 110°C, stirring is continued under nitrogen atmosphere for 4 h, drying is performed under vacuum at 65°C for 10 h, to obtain soybean genistin dianhydride monomer; polyether diol, soybean genistin dianhydride monomer, toluene-2,4-diisocyanate are weighed according to a molar ratio of 1:0.6:2.0; the soybean genistin dianhydride monomer and N,N-dimethylformamide are mixed uniformly according to a mass ratio of 1:6 to prepare a dianhydride solution; the polyether diol and N,N-dimethylformamide are mixed uniformly according to a mass ratio of 1:10, heated to 80°C, toluene-2,4-diisocyanate and 0.06 times the mass of dibutyltin dilaurate of the polyether diol are added in turn under nitrogen atmosphere, stirring is continued at 80°C at 300 r / min for 50 min, the dianhydride solution is added, stirring is continued at 85°C for 1 h, the temperature is raised to 110°C, stirring is continued for 3 h, drying is performed under vacuum at 70°C for 18 h, to obtain functional polyurethane; (2) hexachlorocyclotriphosphazene and acetonitrile are mixed uniformly according to a mass ratio of 1:60, ultrasonic treatment is performed for 2 h at room temperature, 1.2 times the molar amount of 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine of hexachlorocyclotriphosphazene is added, 0.8 times the molar amount of 2-(mercaptomethyl)benzene-1,4-diol of hexachlorocyclotriphosphazene is added, ultrasonic treatment is continued for 20 min, 0.08 times the mass of triethylamine of hexachlorocyclotriphosphazene is added, stirring is performed at 300 r / min for 5 h at 40°C, the temperature is allowed to cool to room temperature naturally, standing is performed for 8 h, filtration is performed, washing is performed with anhydrous ethanol and deionized water for 3 times, drying is performed under vacuum at 60°C for 12 h, to obtain polyphosphazene microspheres; the polyphosphazene microspheres, 4-allyl-2,6-di-tert-butylphenol and N,N-dimethylformamide are mixed uniformly according to a mass ratio of 1:4:30, 0.08 times the mass of azobisisobutyronitrile of the polyphosphazene microspheres is added, stirring is performed at 500 r / min for 4 h at 80°C, filtration is performed, washing is performed with anhydrous ethanol for 5 times, drying is performed under vacuum at 60°C for 18 h, to obtain modified polyphosphazene microspheres; (3) The nano calcium carbonate and anhydrous ethanol were mixed uniformly at a mass ratio of 1:70, and then ultrasonic treatment was performed at room temperature for 2 h. Nano calcium carbonate was added in an amount of 6 times the mass of the nano calcium carbonate, and then the temperature was raised to 80°C and ultrasonic treatment was continued for 8 min. An oxalic acid aqueous solution with a concentration of 1 mol / L was added at a rate of 8 times the mass of the nano calcium carbonate in 10 min, and then stirring was continued for 3 h after the addition was completed. Filtration was performed, and then washing was performed with anhydrous ethanol and deionized water three times each. Drying was performed under vacuum at 70°C for 10 h to obtain pre-modified nano calcium carbonate. The pre-modified nano calcium carbonate, 3-hydroxy-beta-ionone, triethylamine, and N,N-dimethylformamide were mixed uniformly at a mass ratio of 1:4:0.2:30, and then stirring was performed at 65°C and 500 r / min for 5 h. Filtration was performed, and then washing was performed with anhydrous ethanol and deionized water three times each. Drying was performed under vacuum at 70°C for 16 h to obtain modified nano calcium carbonate. (4) The functional polyurethane, the modified polyphosphazene microspheres, and the modified nano calcium carbonate were mixed uniformly, and then extrusion molding was performed in an extruder. The extrusion temperature was 210°C, and the screw rotation speed was 30 r / min. A high-temperature-resistant TPU material was obtained.
[0022] Comparative Example 1 The preparation method of the high-temperature-resistant TPU material of Comparative Example 1 was different from that of Example 2 in step (1). Step (1) was modified as follows: The polyether diol, 1,4-butanediol, and toluene-2,4-diisocyanate were weighed according to a molar ratio of 1:0.55:1.9. The 1,4-butanediol and N,N-dimethylformamide were mixed uniformly at a mass ratio of 1:5.5 to prepare a butanediol solution. The polyether diol and N,N-dimethylformamide were mixed uniformly at a mass ratio of 1:9, and then heating was performed to 75°C. Toluene-2,4-diisocyanate and dibutyltin dilaurate in an amount of 0.05 times the mass of the polyether diol were added in sequence under a nitrogen atmosphere. Stirring was performed at 75°C and 250 r / min for 55 min. The butanediol solution was added, and then stirring was continued at 80°C for 1.5 h. The temperature was raised to 110°C, and then stirring was continued for 2.5 h. Drying was performed under vacuum at 65°C for 19 h to obtain the functional polyurethane. The remaining steps were the same as those of Example 2.
[0023] Comparative Example 2 The preparation method of the high-temperature-resistant TPU material of Comparative Example 2 is different from that of Example 2 in that step (2) is modified as follows: the hexachlorocyclotriphosphazene and acetonitrile are mixed at a mass ratio of 1:60, and are ultrasonically treated for 2 h at room temperature; 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine is added in an amount of 1.2 times the molar amount of the hexachlorocyclotriphosphazene; 2-(mercaptomethyl)benzene-1,4-diol is added in an amount of 0.8 times the molar amount of the hexachlorocyclotriphosphazene; ultrasonic treatment is continued for 20 min; triethylamine is added in an amount of 0.08 times the mass of the hexachlorocyclotriphosphazene; stirring is continued at 40°C and at a speed of 300 r / min for 5 h; the temperature is allowed to cool to room temperature naturally; the mixture is left to stand for 8 h; filtration is performed; the modified polyphosphazene microspheres are washed with anhydrous ethanol and deionized water for 3 times each; and the modified polyphosphazene microspheres are dried at 60°C under vacuum for 12 h. The remaining steps are the same as in Example 2.
[0024] Comparative Example 3 The preparation method of the high-temperature-resistant TPU material of Comparative Example 3 is different from that of Example 2 in that step (2) is not performed, and step (4) is modified as follows: 99 parts by mass of the functionalized polyurethane and 4.5 parts by mass of the modified nano calcium carbonate are mixed uniformly, and are extruded into a shape in an extruder, with an extrusion temperature of 200°C and a screw rotation speed of 25 r / min, to obtain the high-temperature-resistant TPU material. The remaining steps are the same as in Example 2.
[0025] Comparative Example 4 The preparation method of the high-temperature-resistant TPU material of Comparative Example 4 is different from that of Example 2 in that step (3) is not performed, and step (4) is modified as follows: 99 parts by mass of the functionalized polyurethane, 5.5 parts by mass of the modified polyphosphazene microspheres, and 4.5 parts by mass of the nano calcium carbonate are mixed uniformly, and are extruded into a shape in an extruder, with an extrusion temperature of 200°C and a screw rotation speed of 25 r / min, to obtain the high-temperature-resistant TPU material. The remaining steps are the same as in Example 2.
[0026] Comparative Example 5 The preparation method of the high-temperature-resistant TPU material of Comparative Example 5 is different from that of Example 2 in that step (3) is not performed, and step (4) is modified as follows: 99 parts by mass of the functionalized polyurethane and 5.5 parts by mass of the modified polyphosphazene microspheres are mixed uniformly, and are extruded into a shape in an extruder, with an extrusion temperature of 200°C and a screw rotation speed of 25 r / min, to obtain the high-temperature-resistant TPU material. The remaining steps are the same as in Example 2.
[0027] Test Example 1 Test of high-temperature resistance Test method: the thermal stability of the sample was tested by using a Q50 type thermal gravimetric analyzer of TA company of USA. 5 mg of the sample was placed in a crucible, and the temperature was raised from 30℃ to 600℃ at a rate of 10℃ / min under N2 atmosphere, and the 5% thermal weight loss temperature T 5% and the 10% thermal weight loss temperature T 10% of the sample were recorded.
[0028] Table 1
[0029] From the comparison of the experimental data of examples 1-3 and comparative examples 1-5 in table 1, it can be found that the high-temperature-resistant TPU material prepared by the present application has good high-temperature-resistant performance.
[0030] By comparison, the 5% thermal weight loss temperature and the 10% thermal weight loss temperature of examples 1-3 are greater than those of comparative example 1, which shows that the daidzein dianhydride monomer is prepared by the reaction of daidzein and phthalic anhydride-4-formyl chloride; the functional polyurethane is prepared by pre-polymerization of polyether diol and toluene-2,4-diisocyanate, and then chain extension with daidzein dianhydride monomer; the imide group is introduced into the main chain of the functional polyurethane; the introduction of the imide group can improve the high-temperature-resistant performance of the high-temperature-resistant TPU material.
[0031] By comparison, the 5% thermal weight loss temperature and the 10% thermal weight loss temperature of examples 1-3 are greater than those of comparative example 3, which shows that the polyphosphazene microspheres are prepared by the reaction of hexachlorocyclotriphosphazene, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine and 2-(mercaptomethyl)benzene-1,4-diol, so that the polyphosphazene microspheres contain a triazine structure; the triazine structure can improve the flame retardant and high-temperature-resistant performance of the high-temperature-resistant TPU material.
[0032] By comparison, the 5% thermal weight loss temperature and the 10% thermal weight loss temperature of examples 1-3 are greater than those of comparative example 5, which shows that the addition of nano calcium carbonate in the polyurethane can improve the dimensional stability and heat resistance of the material, thereby improving the high-temperature-resistant performance of the high-temperature-resistant TPU material.
[0033] Test example 2 Test of flame retardant performance Test method: the examples and comparative examples were prepared into standard sample strips according to GB / T2406-93, and the limiting oxygen index of the standard sample strips was tested. The results are shown in table 2.
[0034] Table 2
[0035] From the comparison of the experimental data of examples 1~3 and comparative examples 1~5 in table 2, it can be found that the high-temperature-resistant TPU material prepared by the application has good flame retardant performance.
[0036] By comparison, the limiting oxygen index of examples 1~3 is greater than that of comparative example 1, which shows that the daidzein dianhydride monomer is prepared by the reaction of daidzein and phthalic anhydride-4-formyl chloride; the functional polyurethane is prepared by pre-polymerization of polyether glycol and toluene-2,4-diisocyanate, and then chain extension with daidzein dianhydride monomer; daidzein is introduced into the main chain of the functional polyurethane, and daidzein contains a deoxybenzoin structure, which has high carbon-forming ability, so that a dense carbon layer structure can be formed during the combustion process of the material, thereby improving the flame retardant performance of the high-temperature-resistant TPU material.
[0037] By comparison, the limiting oxygen index of examples 1~3 is greater than that of comparative example 3, which shows that the polyphosphazene microspheres are prepared by the reaction of hexachlorocyclotriphosphazene, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine, and 2-(mercaptomethyl)benzene-1,4-diol, so that the cyclotriphosphazene skeleton and the triazine structure are contained in the polyphosphazene microspheres; the triazine structure and the cyclotriphosphazene skeleton can improve the flame retardant performance of the high-temperature-resistant TPU material.
[0038] Test example 3 Test of anti-aging performance Test method: according to GB / T1040.3, the examples and comparative examples are prepared into standard samples, the tensile strength M of the standard samples is tested on an electronic universal testing machine; the standard samples are irradiated under a UV lamp with a power of 200W and a wavelength of 365nm for 15 days, and after the irradiation is completed, the tensile strength N is tested, and the performance retention rate of the standard samples after UV aging is calculated; the performance retention rate=(N / M)×100%, and the results are shown in table 3.
[0039] Table 3
[0040] From the comparison of the experimental data of examples 1~3 and comparative examples 1~5 in table 3, it can be found that the high-temperature-resistant TPU material prepared by the application has good anti-aging performance.
[0041] By comparison, the performance retention rate of examples 1~3 is greater than that of comparative examples 2~3, which indicates that the polyphosphazene microspheres are prepared by the reaction of hexachlorocyclotriphosphazene, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine, and 2-(mercaptomethyl)benzene-1,4-diol, so that the polyphosphazene microspheres contain mercapto groups; the addition reaction of the mercapto groups on the polyphosphazene microspheres and the carbon-carbon double bonds on 4-allyl-2,6-di-tert-butylphenol is carried out to prepare modified polyphosphazene microspheres, and the 2,6-di-tert-butylphenol structure is grafted on the modified polyphosphazene microspheres; the grafted 2,6-di-tert-butylphenol structure belongs to a hindered phenolic light stabilizer, which can delay the photoaging of the material by capturing free radicals and interrupting the oxidation chain reaction, thereby improving the anti-aging performance of the high-temperature-resistant TPU material.
[0042] By comparison, the performance retention rate of examples 1~3 is greater than that of comparative examples 4~5, which indicates that the pre-modified nano calcium carbonate is prepared by the reaction of nano calcium carbonate and chloropropyl triethoxysilane, and the chlorine atom is introduced on the pre-modified nano calcium carbonate; the reaction of the introduced chlorine atom on the pre-modified nano calcium carbonate and the hydroxyl group on 3-hydroxy-beta-ionone is carried out to prepare modified nano calcium carbonate, and the beta-ionone structure is introduced on the modified nano calcium carbonate, the beta-ionone structure has a photoisomerization effect, and it changes from the trans conformation to the cis conformation under the action of ultraviolet light, and returns to the trans conformation under the condition of avoiding light, this reversible cis-trans isomerization change endows the beta-ionone with the performance of ultraviolet absorption, converts the ultraviolet light energy into chemical energy, thereby improving the anti-aging performance of the high-temperature-resistant TPU material.
[0043] The above specific embodiments further illustrate the purpose, technical solutions and beneficial effects of the present application, and it should be understood that the above description is only a specific embodiment of the present application and is not used to limit the protection scope of the present application, any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A high-temperature resistant TPU material, characterized in that, The high-temperature resistant TPU material is prepared by prepolymerizing polyether diol and toluene-2,4-diisocyanate, followed by chain extension with soybean dianhydride monomer to obtain functionalized polyurethane; by reacting polyphosphazene microspheres with 4-allyl-2,6-di-tert-butylphenol to obtain modified polyphosphazene microspheres; by reacting pre-modified nano-calcium carbonate with 3-hydroxy-β-ionone to obtain modified nano-calcium carbonate; and by uniformly mixing the functionalized polyurethane, modified polyphosphazene microspheres, and modified nano-calcium carbonate, followed by extrusion molding. The daidzein dianhydride monomer is prepared by reacting daidzein with phthalic anhydride-4-formyl chloride. The polyphosphazene microspheres were prepared by reacting hexachlorocyclotriphosphazene, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine, and 2-(mercaptomethyl)benzene-1,4-diol. The pre-modified nano-calcium carbonate is prepared by reacting nano-calcium carbonate with chloropropyltriethoxysilane.
2. A method for preparing a high-temperature resistant TPU material, characterized in that, The preparation method of the high-temperature resistant TPU material includes the following preparation steps: (1) Mix soybean aglycone dianhydride monomer and N,N-dimethylformamide evenly to prepare a dianhydride solution; mix polyether diol and N,N-dimethylformamide evenly, heat to 70~80℃, add toluene-2,4-diisocyanate and dibutyltin dilaurate in sequence under nitrogen atmosphere, react at 70~80℃ for 50~60min, add dianhydride solution, continue to react at 75~85℃ for 1~2h, raise the temperature to 110℃, continue to react for 2~3h to obtain functionalized polyurethane; (2) Mix polyphosphazene microspheres, 4-allyl-2,6-di-tert-butylphenol and N,N-dimethylformamide evenly, add azobisisobutyronitrile, and react at 70~80℃ for 4~5h to obtain modified polyphosphazene microspheres; (3) Mix pre-modified nano-calcium carbonate, 3-hydroxy-β-ionone, triethylamine and N,N-dimethylformamide evenly, and react at 55~65℃ for 5~6h to obtain modified nano-calcium carbonate; (4) The functionalized polyurethane, modified polyphosphazene microspheres and modified nano calcium carbonate are mixed evenly and extruded in an extruder to obtain high temperature resistant TPU material.
3. The method for preparing a high-temperature resistant TPU material according to claim 2, characterized in that, The preparation method of the daidzein dianhydride monomer in step (1) is as follows: daidzein and phthalic anhydride-4-formyl chloride are added to toluene in a molar ratio of 1:2, pyridine is added, the mixture is stirred at room temperature for 60-70 min, the temperature is raised to 100-110℃, and the reaction is continued for 4-5 h under a nitrogen atmosphere to obtain the daidzein dianhydride monomer.
4. The method for preparing a high-temperature resistant TPU material according to claim 2, characterized in that, The molar ratio of polyether diol, soybean dianhydride monomer, and toluene-2,4-diisocyanate in step (1) is 1:(0.5~0.6):(1.8~2.0).
5. The method for preparing a high-temperature resistant TPU material according to claim 2, characterized in that, The preparation method of the polyphosphazene microspheres in step (2) is as follows: hexachlorocyclotriphosphazene and acetonitrile are mixed evenly and ultrasonically dispersed at room temperature. 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine and 2-(mercaptomethyl)benzene-1,4-diol are added and ultrasonic dispersion is continued. Triethylamine is added and the mixture is stirred at 30~40℃ for 5~6h to obtain polyphosphazene microspheres.
6. The method for preparing a high-temperature resistant TPU material according to claim 2, characterized in that, The mass ratio of the polyphosphazene microspheres and 4-allyl-2,6-di-tert-butylphenol in step (2) is 1:(3~4).
7. The method for preparing a high-temperature resistant TPU material according to claim 2, characterized in that, The preparation method of the pre-modified nano calcium carbonate in step (3) is as follows: mix nano calcium carbonate and anhydrous ethanol evenly, disperse ultrasonically at room temperature, add chloropropyltriethoxysilane, heat to 70~80℃, continue ultrasonic dispersion, add oxalic acid aqueous solution dropwise, and continue reaction for 3~4 hours after the addition is completed to obtain pre-modified nano calcium carbonate.
8. The method for preparing a high-temperature resistant TPU material according to claim 2, characterized in that, The amounts of functionalized polyurethane, modified polyphosphazene microspheres, and modified nano-calcium carbonate in step (4) are as follows: by mass parts, functionalized polyurethane 98-100 parts, modified polyphosphazene microspheres 5-6 parts, and modified nano-calcium carbonate 4-5 parts.
9. The method for preparing a high-temperature resistant TPU material according to claim 2, characterized in that, The extrusion temperature in step (4) is 190~210℃ and the screw speed is 20~30r / min.
Citation Information
Patent Citations
Controlled expansion balloon catheter
CN101808599A
Electromagnetic absorption polyurethane membrane material and preparation method thereof
CN118459976A
Preparation method of self-repairing polyurethane material and application of self-repairing polyurethane material in tire tube
CN118725545A
Process for preparing flame-retardant polyethylene plastic by recycling waste polyethylene plastic
CN120441984A
Use of a stabilizer composition for stabilizing organic materials, stabilizer composition, masterbatch, composition, molding compound of the molded parts, process for the oxidative, thermal actinic stabilization of a thermoplastic polymer, and use of a composition
DE102021202102A1